Harmonizing analytical chemistry and clinical epidemiology for human biomonitoring studies. A case-study of plastic product chemicals in urine. (January 2020) - Heffernan, A.L.; Gomez-Ramos, M.J.; Symeonides, C.; Hare, D.J.; Vijayasarathy, S.; Thompson, K.; Mueller, J.F.; Ponsonby, A.L.; Sly, P.D.; ,
Abstract: There is an interdisciplinary interface between analytical chemistry and epidemiology studies with respect to the design, execution, and analysis of environmental epidemiology cohorts and studies. Extracting meaningful results linking chemical exposure to human health outcomes begins at study design and spans the entire workflow. Here we discuss analytical experimental design from an exposure science perspective, and propose a reporting checklist for the design of human biomonitoring studies. We explain key analytical chemistry concepts of blanks and limits of reporting and present a case series of plastic product chemical exposure in prenatal urine specimens from the Barwon Infant Study. Highlights: Analytical chemistry and epidemiology should both inform experimental design. Sample collection and processing can contribute to analytical contamination. Analytical blanks and limits of reporting play an important role in quality control. Case study of urinary phthalate and bisphenol analogues in the Barwon Infant Study.